Provision of infracstructure as a strategy towards rural development: a comparative analysis of Gbongan, Akiriboto, Osu and Ibodi - Akeredolu, Oluwapelumi Kolawole (Urban & Regional Planning, Obafemi Awolowo University, Ile Ife, Nigeria, 2020)
124p